Defining targets to improve care delivery for T4 larynx squamous cell carcinoma - Catherine H. Frenkel; Daniel S. Brickman; Sally J. Trufan; Matthew C. Ward; Benjamin J. Moeller; Daniel R. Carrizosa; Ashley L. Sumrall; Zvonimir L. Milas (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective United States oncology trends consistently demonstrate that nearly half of T4a larynx carcinoma patients are treated with larynx preservation, despite national guidelines favoring laryngectomy. This study identifies clinical decision‐making drivers and defines patient subsets that should become targets for care improvement. Methods Retrospective analysis of patients with cT4 squamous cell carcinoma of the larynx from US National Cancer Database 2005–2016. Demographic data and survival rates between clinical pathways were compared. Survival was estimated by Kaplan–Meier method with statistical comparisons assessed by log‐rank test. Results Of 11,556 patients with cT4 disease, laryngectomy (TL) was the initial treatment for 4627 (40%) patients. Larynx preservation via chemoradiation (CRT) occurred for 4307 patients. TL and CRT patients had similar Charlson–Deyo comorbidity indices and insurance status. TL patients had higher total tumor size, lower N3 rates and were more often seen at academic institutions (p < .0001). N0 surgery patients with adjuvant treatment demonstrated superior median survival (MS) compared to CRT (surgery + radiation MS: 69 months, surgery + chemoradiation MS: 66, CRT MS: 37.7), p < .0001. MS for N1/N2 disease patients was 56.5 months for surgery + radiation and 35.5 months for surgery + CRT, superior to CRT, MS 30.8 months, p < .0001. Tri‐modality N3 patients with up front surgery had similar MS compared to CRT (surgery + chemoradiation 21.3 months vs. CRT 16.1), p = .95. Conclusion National quality improvement initiatives are needed to promote guideline adherence and improve survival in advanced larynx cancer. Targets for such initiatives should be patients with limited or no nodal disease burden, that meet clear T4a imaging criteria. Level of Evidence Level IV, non‐randomized controlled cohort.